2021
DOI: 10.1037/ccp0000695
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-delivered multicomponent lifestyle medicine intervention for depressive symptoms: A randomized controlled trial.

Abstract: Objective: To evaluate the efficacy and credibility of a smartphone-delivered multicomponent lifestyle medicine (LM) intervention, Lifestyle Hub, as a primary modality for managing depressive symptoms in an adult Chinese population. Method: Participants with at least a moderate level of depressive symptoms (n = 79), as indicated by a Patient Health Questionnaire-9 score of ≥10, were randomly assigned to an LM intervention group (LMG; n = 39; eight weekly sessions) or a waitlist control group (WLG; n = 40). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 86 publications
(133 reference statements)
1
34
2
Order By: Relevance
“…Given the potential merit of smartphone-delivered interventions in managing CMDs, a pioneering smartphone-delivered LM intervention, Lifestyle Hub, was developed ( 21 ). The efficacy of Lifestyle Hub in ameliorating depressive symptoms has previously been evaluated in a Chinese adult population with at least moderate levels of depressive symptoms ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential merit of smartphone-delivered interventions in managing CMDs, a pioneering smartphone-delivered LM intervention, Lifestyle Hub, was developed ( 21 ). The efficacy of Lifestyle Hub in ameliorating depressive symptoms has previously been evaluated in a Chinese adult population with at least moderate levels of depressive symptoms ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential merit of smartphone-delivered interventions in managing CMDs, a pioneering smartphone-delivered LM intervention, Lifestyle Hub, was developed ( 21 ). The efficacy of Lifestyle Hub in ameliorating depressive symptoms has previously been evaluated in a Chinese adult population with at least moderate levels of depressive symptoms ( 21 ). The results suggested that Lifestyle Hub was efficacious in improving depressive and anxiety symptoms with moderate to large effect sizes compared to a waitlist (WL) control group at immediate post-intervention assessment ( d = 0.66–0.93).…”
Section: Introductionmentioning
confidence: 99%
“…The Short Form (Six-Dimension) Health Survey (SF-6D; Lam et al, 2008) was used to measure quality of life, including physical functioning, role limitation, social functioning, bodily pain, mental health, and vitality. The SF-6D showed good reliability (Cronbach's α = .80; V. W. H. Wong et al, 2021).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…After removing 807 duplicates, 1321 studies were screened using titles and abstracts, and 115 studies were identified for full-text screening. With the exclusion of 102 irrelevant studies, 13 studies 29,[31][32][33][38][39][40][41][42][43][44][45][46] evaluating 16 intervention apps were included in the analysis (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Of 13 included studies, 6 studies 29,32,[39][40][41]44 had a high ROB and 7 studies 31,33,38,42,43,45,46 demonstrated some concerns of ROB (eFigure 1 and eFigure 2 in Supplement 1). Major sources of bias were the use of self-report questionnaires for outcome measures and the complications of using the double-blind trials.…”
Section: Quality Assessmentmentioning
confidence: 99%